Analysis of Green Moral Obligation on Intention to Adopting Electric Vehicles (EV) with Openness to Changes and Self Enhancement as Moderating Variables - Purwanto, Sugeng; Rini, Hesty Prima (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this research is to predict and analyze the influence of Green Moral Obligation on consumers' intention to adopt EV (electric vehicle)s in Indonesia, with Self Enhancement and Openness to Change as moderating variables. The research subjects are driving consumers distributed across the entire territory of the Republic of Indonesia, with a sample size of 250 respondents distributed through online questionnaires using convenience sampling technique. The data analysis tool used SEM-PLS (SEM-Partial Least Squares). The results of this research indicate that the Green Moral Obligation variable has a significant impact on the intention to adopt electric vehicles, and the Self Enhancement and Openness to Change variables have been proven to positively moderate the relationship between Green Moral Obligation and the intention to adopt electric vehicles. This research is expected to be used for policy development in the automotive industry, as a reference for academics and researchers for further research or theory development.